Novo arranjo para inovação nas instituições científicas, tecnológicas e de inovação (ICT): ambiente temático catalisador de inovação (ATCI) e a experiência da UFMG - Juliana Corrêa Crepalde Medeiros (2020)
This study aimed at elaborating and testing an innovation arrangement for Institutions of Science, Technology, and Innovation (ICTs) with companies and other institutions involved in the National Innovation System (SNI). The theoretical model proposed in this thesis is a species in the innovation-promoting environment genre, and was entitled Thematic Environment for Innovation Catalysis (ATCI). The proposal is based on the premise of making the most of the skills accumulated in the ICTs in form of intellectual capital, technologies (intellectual property) and research infrastructures in certain technological areas, such as biotechnology, nanotechnology, artificial intelligence, environmental technologies, energy, new materials, and others to advance the innovative capacity of the companies. ATCI can be an instrument to strengthen the internal environment of innovation and entrepreneurship of ICTs. ATCI is supported by the recent Legal Framework for Science, Technology and Innovation (MLCTI) in Brazil, and can be formalized either by means of a legal instrument, or by the constitution of a legal person, contemplating the participation of ICTs and the institutions that take part in the ATCI. This study discusses herein how to treat aspects such as budget, personnel, governance, and environmental management, considering the two possibilities of legal formatting. The model was tested in two cases at Universidade Federal de Minas Gerais (UFMG). One case arises from the accumulation of experience in services for hire and the other in research and development activities. The first case is the ATCI formed between the Fuel Testing Laboratory (LEC) at UFMG and Companhia de Desenvolvimento de Minas Gerais (CODEMGE), in the thematic area of aviation fuels. This case study showed that the role of LEC in providing technological services over more than twenty years was an important way for the laboratory to develop competences and skills, both technical and industry-related, which allowed LEC to move forward to more complex partnerships, aiming at developing new technological solutions. As a result, the study proposes a possible path for implementing ATCIs that employ the skills obtained by ICTs with their experience in providing services for hire. The second case concerns the ATCI formed between Midas National Institute of Science and Technology (INCT-Midas), coordinated by UFMG, and the Center for Innovation and Technology (CIT-SENAI), in the thematic area of environmental technologies. This case study discusses the constitution of an ATCI from research groups that have been acting in Research, Development and Innovation (RD&I), and intend to move towards more advanced models of interaction with the industry, such as scaling up, proof of concept and prototyping, which can facilitate technology transfer for companies. These two cases with different characteristics allowed to evaluate and test how the new arrangement proposed in this thesis behaves in different ICT contexts. This research also investigated the experience of UFMG in the management of Science, Technology and Innovation (CT&I), as a relevant aspect for the adoption of new arrangements, and demonstrates the importance of ICTs to organize their innovation and entrepreneurial environment in order to expand their contribution to the SNI.